Influence of foliar application of algae extract and amino acids mixture on fenugreek plants in sandy and clay soils - SHAHIRA A. TARRAF; IMAN M. TALAAT; ABO EL-KHAIR B. EL-SAYED; LAILA K. BALBAA (Nusantara Bioscience, 2015)
Abstract. Tarraf SA, Talaat IM, El-Sayed AEB, Balbaa LK. 2015. Influence of foliar application of algae extract and amino acids mixture on fenugreek plants in sandy and clay soils. Nusantara Bioscience 7: 33-37. Two pot experiments were conducted to study the effect of foliar application of algae extract and amino acids mixture on the growth and chemical constituents of fenugreek plants (Trigonella foenum-graecum L.). Plants were sprayed with different concentrations of algae extract (0.0, 2.5, 5.0 g/L) or equivalent of amino acids mixture (0.0, 0.625, 1.25 g/L). The results indicated that foliar application of amino acids mixture enhanced the vegetative growth of fenugreek plants, especially when plants were sprayed with 1.25 g/L amino acids mixture. Data also show that total nitrogen, essential oil percentage, and yield followed the same trend. These results hold true for plants cultivated in either clay soil or sandy soil. Data also indicated that foliar application of algae extract to fenugreek plants significantly increased plant height, number of leaves, number of branches and fresh and dry weights of plant at vegetative growth stage and flowering stage of fenugreek plant, especially in plants treated with 5 g/L algae extract in sandy and clay soils, respectively. Treatment of fenugreek plants with algae extract markedly increased nitrogen, phosphorous and potassium contents, especially at 5 g/L.